Assessment of permeability of eroded dentin after the use of universal, self-etch, and conventional systems - Roma, Fábia R. V. O.; Penha, Karla J. S.; Torres, Carlos R. G. [UNESP]; Maia-Filho, Etevaldo M.; Firoozmand, Leily M. (Sociedad Argentina de Investigacion Odontologica, 2021)
Dentin hypersensitivity is caused by increased dentinal permeability due to total or partial exposure of dentinal tubules, which in turn can be produced by alterations of dental structures or failure of restorative procedures. The purpose of this in vitro study was to evaluate the efficacy of the application of different kinds of adhesive systems to prevent dentin permeability before and after an erosive challenge. Fifty bovine dentin discs (6x1 mm) were prepared and the specimens were divided into 5 groups (n=10): (SB2) Single Bond 2, (SBU) Universal Single Bond, (CSB) Clearfil SE Bond, (SM) Scotchbond Multipurpose and (C) Control. Hydraulic conductance of dentin was recorded after adhesive application (HC-1) and after erosive challenge (HC-2). Dentin surface images of post-treatment and post-erosive challenge were obtained by scanning electron microscopy (SEM). Data were analyzed using Kruskal Wallis, Mann-Whitney with Bonferroni correction and Wilcoxon tests (p<0.05). Reduction in dentin permeability was observed with the application of adhesive systems (p<0.05). After the erosive challenge, dentin permeability increased for SBU and CSB (p<0.05), while SB2 and SM did not differ in HC-1 or HC-2 (p>0.05). The conventional, self-etching and universal adhesive systems reduce dentinal permeability by more than 80%, and dentin demineralization may contribute to the increased permeability of universal and self-etching systems.
Avaliação da permeabilidade da dentina com erosão, após o uso de sistemas universais, autocondicionantes e convencionais
Keywords: dentin; dentin bonding agents; dentin permeability; tooth erosion